Changes in visceral adipose tissue mitochondrial content with type 2 diabetes and daily voluntary wheel running in OLETF rats - Laye, Matthew J.; Rector, R. Scott; Warner, Shana O.; Naples, Scott P.; Perretta, Aspen L.; Uptergrove, Grace M.; Laughlin, M. Harold; Thyfault, John P.; Booth, Frank W.; Ibdah, Jamal A. (The Journal of physiology, 2009)
Using the hyperphagic, obese, Otsuka LongâEvans Tokushima Fatty (OLETF) rat, we sought to determine if progression to type 2 diabetes alters visceral white adipose tissue (WAT) mitochondrial content and if these changes are modified through prevention of type 2 diabetes with daily exercise. At 4 weeks of age, OLETF rats began voluntary wheel running (OLETF-EX) while additional OLETF rats (OLETF-SED) and LongâEvans Tokushima Otsuka (LETO-SED) rats served as obese and lean sedentary controls, respectively, for 13, 20 and 40 weeks of age ( n = 6â8 for each group at each age). OLETF-SED animals displayed insulin resistance at 13 and 20 weeks and type 2 diabetes by 40 weeks. OLETF-SED animals gained significantly ( P < 0.001) more weight and omental fat mass compared with OLETF-EX and LETO-SED. Markers of WAT mitochondrial protein content (cytochrome c , COXIV-subunit I, and citrate synthase activity) significantly increased ( P < 0.05) from 13 to 40 weeks in the LETO-SED, but were significantly attenuated in the OLETF-SED rats. Daily exercise normalized WAT cytochrome c and COXIV-subunit I protein content in the OLETF-EX to the healthy LETO-SED animals. In conclusion, increases in omental WAT mitochondrial content between 20 and 40 weeks of age in LETO control animals are attenuated in the hyperphagic, obese OLETF rat. These alterations occurred in conjunction with the progression from insulin resistance to type 2 diabetes and were prevented with daily exercise. Reduced ability to increase WAT mitochondrial content does not appear to be a primary cause of insulin resistance, but may play a key role in the worsening of the disease condition.